Explore the Paths and Strategies for Integrating Red Culture into Physical Education in Higher Vocational Colleges in Hubei Province in the New Era - Xue, Cao (Pacific International Journal, 2024)
Physical education in higher vocational colleges in Hubei province, as an important part of cultivating young students’ physical and mental health, how to integrate into the red culture in the new era and lead students to the correct life road is a topic worth exploring. Through literature review, this paper reviews the current situation and trends of red culture research at home and abroad, and discusses the path and strategy of integrating red culture into physical education of higher vocational colleges in Hubei in the new era. By analyzing the current situation of physical education and studying the connotation and value of red culture and red sports in the new era, the paper puts forward the path of integrating into red culture in the new era, and makes corresponding strategies. This will help enrich the connotation of physical education in schools and cultivate students’ patriotic feelings and social responsibility.